The MAK‐Collection for Occupational Health and Safety 2016
DOI: 10.1002/3527600418.am8477e1816
|View full text |Cite
|
Sign up to set email alerts
|

Phthalates, long‐chain (diisononyl phthalate, di‐n‐decyl phthalate, diisodecyl phthalate, diundecyl phthalate and didodecyl phthalate) [Air Monitoring Methods, 2014]

Abstract: This analytical method is a validated measurement procedure for the determination of long‐chain phthalates such as diisononyl phthalate, di‐n‐decyl phthalate, diisodecyl phthalate, diundecyl phthalate and didodecyl phthalate present in the workplace air in the gaseous and particulate state. Sampling is performed by drawing a defined volume of air through a cellulose acetate filter located in the sampling head with an adsorption tube filled with silica gel connected downstream using a suitable pump. The flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Didodecyl phthalate (DDP) is a lipophilic, colourless, water-insoluble liquid and is widely used in the production of PVC as a plasticiser. Didodecyl phthalate is one among four important phthalates commonly found in the environment (Hahn et al, 2016). Didodecyl phthalate has been analysed by J-U Hahn et al, 2014 as one of the major long chained phthalates compounds commonly found in the environment because of its wide application.…”
Section: Introductionmentioning
confidence: 99%
“…Didodecyl phthalate (DDP) is a lipophilic, colourless, water-insoluble liquid and is widely used in the production of PVC as a plasticiser. Didodecyl phthalate is one among four important phthalates commonly found in the environment (Hahn et al, 2016). Didodecyl phthalate has been analysed by J-U Hahn et al, 2014 as one of the major long chained phthalates compounds commonly found in the environment because of its wide application.…”
Section: Introductionmentioning
confidence: 99%